PENINGKATAN PEMAHAMAN KONSEP MATERI EKOSISTEM DALAM MATA PELAJARAN IPAS SISWA KELAS III SEKOLAH DASAR GMIT OEPURA MELALUI PENGGUNAAN MEDIA PEMBELAJARAN POP UP BOOK - Maria Eugenia Sabu Unaradjan; Antonius Suban Hali; Netty E. A. Nawa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted due to the low conceptual understanding of students on ecosystem material in Class III B at SD GMIT Oepura Kupang. This condition was reflected in the students’ daily test results, where most of them had not yet achieved the Minimum Mastery Criteria for Learning Objectives (KKTP). In addition, students showed low participation during the learning process, which affected their learning outcomes. Therefore, this study aimed to improve students’ conceptual understanding through the use of Pop-Up Book learning media on ecosystem material. The method used in this study was Classroom Action Research (CAR), which was carried out in two cycles. Each cycle consisted of planning, action implementation, observation, and reflection stages. The subjects of this study were 26 students. Data collection techniques included observations of teacher and student activities as well as learning outcome tests to determine the improvement of students’ conceptual understanding. The results of the study showed improvements in both learning outcomes and student activities in each cycle. In the pre-cycle stage, the learning mastery percentage was only 34.62%, with 9 students achieving mastery and 17 students not yet achieving mastery. After the implementation of Pop-Up Book media in Cycle I, learning mastery increased to 61.53%, with 16 students achieving mastery and 10 students not yet achieving mastery. Furthermore, in Cycle II, learning mastery increased significantly to 88.46%, with 23 students achieving mastery and only 3 students not yet achieving mastery, thereby meeting the success indicator of ≥ 85%. Student activity also improved from an average score of 67 in Cycle I to 81 in Cycle II. Thus, the Pop-Up Book learning media proved effective in improving students’ conceptual understanding and learning outcomes on ecosystem material.